Time Is on Our Side: Temporal Agency in Courtship Narratives. Issue 7 (3rd October 2018) - Kurlak, Rebecca M.; McGlone, Matthew S.; Vangelisti, Anita L.
ABSTRACT: The reported study investigated how newlyweds linguistically encode changes in relationship commitment in retrospective courtship narratives. In particular, we explored their use of emotion words and its correspondence with "temporal agency, " that is, the attribution of temporal change to human actors or to abstract events and processes. A corpus of courtship narratives composed by recently married participants was analyzed. Narrators used a higher frequency of positive emotion terms (e.g., wonderful ) and human temporal agency assignments (e.g., We spent Thanksgiving together ) to describe episodes they associated with an increase in relationship commitment from others they associated with a decrease. When describing increases in commitment, their expression of positive emotion partially mediated human temporal agency assignments. However, they did not use significantly more negative emotion words (e.g., sad ) or abstract temporal agency assignments (e.g., Our relationship went through a tough period ) to describe decreases in commitment than increases. The implications of these findings for relational discourse analysis and embodiment theory are considered.